Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 24 Jun 2016, 20:39

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Root

 post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
Director
Joined: 12 Jun 2006
Posts: 532
Followers: 2

Kudos [?]: 80 [0], given: 1

### Show Tags

31 Aug 2007, 12:51
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

I picked #s here. Generally, I don't like doing this. Does anyone have a faster method?

If one root of the equation is 2x^2 + 3x - k= 0 is 6, what is the value of k?

90
42
18
10
-10
VP
Joined: 10 Jun 2007
Posts: 1459
Followers: 7

Kudos [?]: 207 [0], given: 0

### Show Tags

31 Aug 2007, 14:16
ggarr wrote:
I picked #s here. Generally, I don't like doing this. Does anyone have a faster method?

If one root of the equation is 2x^2 + 3x - k= 0 is 6, what is the value of k?

90
42
18
10
-10

90

2x^2 +3x - k = (x-6)*(2x-a) = 2x^2 - ax-12x + 6a
= 2x^2 + x(-a-12) + 6a

-a-12 = 3
a = -15

6a = -k
6*(-15) = -k
k = 90
VP
Joined: 08 Jun 2005
Posts: 1146
Followers: 6

Kudos [?]: 164 [0], given: 0

### Show Tags

31 Aug 2007, 14:20
2x^2 + 3x - k = 0

using the Quadratic Formula

x = (-b ± sqrt(b^2-4*a*c))/2*a

x = (-3 ± sqrt(3^2-4*2*-k))/2*2

x = (-3 ± sqrt(9-8*-k))/4

one solution is given as 6 so:

6 = (-3 + sqrt(9-8*-k))/4

24 = -3 + sqrt(9-8*-k)

27*27 = 9-8*-k

720 = 8*k

k = 90

the answer is (A)

Senior Manager
Joined: 19 Feb 2007
Posts: 325
Followers: 1

Kudos [?]: 34 [0], given: 0

### Show Tags

01 Sep 2007, 12:28
If 6 is the root, the equation should be satisfied for x= 6.

Putting x= 6 in equation.

2(6)^2 +3(6) - k = 0

72 + 18 - k =0

=> k = 90.

The ans is (A).

10 sec max
[#permalink] 01 Sep 2007, 12:28
Display posts from previous: Sort by

# Root

 post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.